Women In The Modern Workplace : Gender Barriers To Business Start-Ups. (Cambridge Scholars Publishing, 2009)
The primary focus of this research is to examine the process of venture creation among women in Ireland and the dynamics at play, which affect the nascent female entrepreneur as she embarks on this process. A fundamentally explorative study, this research addresses idea formulation, motivations for business start-up, the start -up process and the challenges or barriers explicit to the nascent female entrepreneur. This study examines three nascent female entrepreneurs who are in the process o ...